1997
DOI: 10.1080/01635589709514499
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of multiple micronutrient supplementation in the management of oral submucous fibrosis in Karachi, Pakistan

Abstract: Oral submucous fibrosis (OSF) is an oral precancerous condition characterized by symptoms such as intolerance to spicy food, altered salivation, progressive difficulty in opening the mouth, and signs like vesiculation, ulceration, blanching, rigidity, and stiffening of the oral mucosa and depapillation and altered mobility of the tongue. It is seen mostly among people of Indian subcontinent origin. The major structural change is extensive fibroelastic scarring of the lamina propria and deeper connective tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 16 publications
6
59
1
Order By: Relevance
“…In our study the distribution of the individuals was based on the mean age which was 33.71 years. It was noted that the age group between 19 and 34 years were in majority in the study group, which was similar to studies by Rupak et al, Katharia et al and Maher et al [19][20][21]. More than 64% of cases were below 35 years of age in accordance with a study by Sinor et al [22].…”
Section: Discussionsupporting
confidence: 81%
“…In our study the distribution of the individuals was based on the mean age which was 33.71 years. It was noted that the age group between 19 and 34 years were in majority in the study group, which was similar to studies by Rupak et al, Katharia et al and Maher et al [19][20][21]. More than 64% of cases were below 35 years of age in accordance with a study by Sinor et al [22].…”
Section: Discussionsupporting
confidence: 81%
“…Enrolled populations had a wide spectrum of OSF (i.e. from early to advanced), and yet stratification of the study group by OSF stage ⁄ severity rating was defined at baseline in only approximately half of the studies, most of these by reporting baseline mouth opening, although some studies grouped subjects by range of opening (Ariyawardana et al, 2005), (Maher et al, 1997) and (Lai et al, 1995), or by using various rating scales (Khanna and Andrade, 1995), (Gupta et al, 1992), (Talsania et al, 2009) and .…”
Section: Resultsmentioning
confidence: 99%
“…[63] Another study by (Maher et al) evaluated the efficacy of combination of micronutrients (Vitamins A, B complex, C, D, and E) and minerals (iron, calcium, copper, zinc, magnesium, and others) in controlling the symptoms and signs of OSMF. [64] Significant improvement in symptoms, notably intolerance to spicy food, burning sensation, and mouth opening, was observed at exit. Borle et al, (18) reported that Vitamin A, 50,000 IU chewable tablets, if given once daily could cause symptomatic improvement.…”
Section: Cessation Of Habitmentioning
confidence: 98%